[PP.15.19] COST-EFFECTIVENESS OF ANGIOTENSIN RECEPTOR BLOCKERS IN PATIENTS WITH UNCOMPLICATED HYPERTENSION: A COMPARATIVE ANALYSIS USING CLINICAL AND DRUGS UTILIZATION DATA. (September 2017) - Mazza, A.; Schiavon, L.; Rossetti, C.; Sacco, A.P.; Bregola, G.; Contato, E.; Ramazzina, E.
Abstract : Objective: Health benefits and related cost savings are achieved optimizing treatment of hypertensive patients (HTs). The aim of this study was to evaluate the costs and cost-effectiveness of treatment with angiotensin II receptor blockers (ARBs) in HTs with uncomplicated essential hypertension and to compare the costs and percentage share of prescription associated with ARBs to reach blood pressure (BP) control. Figure. No caption available. Design and method: Costs of the ARBs was estimated based on pharmacy dispensing records and the BP-lowering effects of candesartan, irbesartan, losartan, olmesartan, telmisartan and valsartan was evaluated retrospectively. In details, 114 HTs (mean age 59.4 ± 13.5, 57.5% men) taking anti-hypertensive therapy with ARBs, and consecutively referred to our Hypertension Centre from November 2105 to November 2016 has been evaluated. The BP-lowering effect of ARBs as in monotherapy than combined with hydrochlorothiazide at the doses commonly used in the market to reach BP control (i.e. BP <140/90 mmHg) was analyzed. Office BP was evaluated at baseline and after an average of 6-month follow-up consulting the medical fields. Analysis of variance for repeated measures was provided. Results: At baseline office BP was not different between ARBs. Treatment with candesartan (7, 9% of HTs) and olmesartan (34, 5% of HTs) versus other ARBs resulted in a significantly decrease of systolic BP (SBP) and diastolic BP (DBP) as for monotherapy than for combination therapy (Figure). Cost effectiveness for olmesartan, that is still the only ARBs inthe market without expired patent, was estimated for all treated HTs at euro 5, 466 compared to euro 565 for cansedartan, respectively. Conclusions: Candesartan was estimated to be the most favorable option in terms of cost-effectiveness. These data have some limitations, but open the question if candesartan treatment should be preferred to olmesartan in this clinical setting, and even in to switch anti-hypertensive treament to candesartan when systolic BP is uncontrolled with olmesartan. However, for definite conclusions to be drawn, this hypothesis-generating study requires confirmation from further prospective studies comparing ARBs based on their effect on BP control and hard endpoints.